Preventive effect of long-term aldose reductase inhibition (ponalrestat) on nerve conduction and sural nerve structure in the spontaneously diabetic Bio-Breeding rat. - Sima, A A (1990)
To test the hypothesis that aldose reductase inhibition may prevent or delay the development of functional and structural neuropathy in the insulin-deficient diabetic Bio-Breeding rat (BB-rat), hyperglycemic rats were begun on the aldose reductase inhibitor (ARI) ponalrestat 25 mg/kg body wt soon after the onset of diabetes and followed for 4 or 6 mo. Ponalrestat treatment completely prevented the characteristic nerve conduction slowing and structural abnormalities of the node of Ranvier for 4 mo despite only partial preservation of axonal integrity. Ponalrestat treatment for 6 mo achieved a partial but significant prevention of nerve conduction slowing, axoglial dysjunction, and axonal degenerative changes. This incomplete but significant prevention of neuropathy by ponalrestat suggests that additional mechanisms besides polyol-pathway activation may be of importance in the pathogenesis of diabetic neuropathy. Alternatively, the dosage used in the present study may not have been sufficient to achieve a complete prevention. Despite the only partial protective effect of ARI treatment on degenerative peripheral nerve changes in hyperglycemic BB-rats, 6 mo of treatment resulted in a more than threefold increase in regenerating nerve fibers. These data suggest that prophylactic ARI treatment may be efficacious in delaying the development of diabetic neuropathy.